Possible patterns of epidermal melanocyte disappearance in nonsegmental vitiligo: a clinicopathological study. (1st February 2015) - Benzekri, L.; Hmamouchi, I.; Gauthier, Y.
Summary: Background: The depigmentation of vitiligo results in a progressive and chronic melanocyte loss with rare melanocytes occasionally remaining in the epidermis or the hair follicle reservoirs. Destruction by immune infiltrates in close contact with melanocytes within microvesicles and/or detachment of melanocytes followed by their transepidermal elimination should be regarded as possible mechanisms of chronic loss of pigment cells. Objectives: To assess the frequency of these two histological findings and to establish a direct correlation with clinical features. Methods: This was a prospective observational study that took place over 1 year. Each patient received a standardized evaluation that included daylight and Wood's lamp examinations, pictures, biopsies performed on the marginal area, and histological and immunohistological studies. A second examination to assess the activity of the lesions was performed 1 year after inclusion in the study. Clinical changes associated with microvesicles were compared with those associated with detached melanocytes from the basal layer. Results: This study included 50 patients. The histological findings were classified as inflammatory with isolated microvesicles (29 cases), noninflammatory with only detached melanocytes from the basal layer (12 cases) and a combination of coexisting microvesicles and detached melanocytes (six cases). Correlations were obtained between the histological findings and clinical features (aspect and activity of the lesions) and E‐cadherin expression. Conclusions: Our data suggest the existence of two patterns of melanocyte disappearance in nonsegmental vitiligo.